A novel solar thermal polygeneration system for sustainable production of cooling, clean water and domestic hot water in United Arab Emirates: Dynamic simulation and economic evaluation. (1st April 2016) - Mohan, Gowtham; Kumar, Uday; Pokhrel, Manoj Kumar; Martin, Andrew
Graphical abstract: Highlights: A new polygeneration system is proposed to simultaneously produce cooling, clean water and domestic hot water. Membrane distillation systems and absorption chillers are integrated to develop a novel solar thermal polygeneration system. The polygeneration system is optimized to maximize the system efficiency and minimize investment costs. Complete energy, economic and environmental benefits of the polygeneration system is investigated. Abstract: In this paper, a novel solar thermal polygeneration (STP) system for production of cooling, clean water and domestic hot water is modeled and analyzed for the weather conditions of United Arab Emirates (UAE). The system comprises of solar collectors for production of thermal energy, single stage LiBr–H2 O absorption chiller (VAC) for providing air conditioning to office cabins and membrane distillation (MD) modules for clean water production along with domestic hot water generation as by-product. The performance of STP is analyzed with three different solar collectors – flat plate collectors (FPC), evacuated tube collector (ETC) and compound parabolic collector (CPC). The system is modeled and dynamically simulated using TRNSYS software for optimization of various design parameters like slope of the collectors, mass flow rate through the collector loop, storage capacity and area of collectors. Combined and system efficiency of the STP system has been determined for optimum conditions. Economic benefits are analyzed for different collectors and fuel costs savings. A lowest payback period of 6.75 years is achieved by STP with evacuated tube collector field having gross area of 216 m 2 . STP system has cumulative savings of 520, 000 over the life time of the project through roof top solar collector installation. In terms of environmental benefits, 109 metric tons/year of CO2 emissions would be avoided and hence the overall payback period would be reduced by 8% based on cost saving through carbon credits. Economic and environmental benefits were aided by steady system performances of absorption chiller (35 kW), membrane distiller (80 l/day) and heat recovery system (1.2 m 3 /h) throughout the year. The complete simulation results of the STP system is utilized for the development, installation and testing of a polygeneration system at RAKRIC.